Utilizing recycled rubber in concrete: a study of some properties (Journal of Pure & Applied Sciences, 2023)
This paper investigates the effects of adding recycled rubber to concrete in terms of its physical and mechanical properties. The study involved three mixes of concrete created by replacing the gravel with recycled rubber particles with varying percentages of rubber by volume, 10%, 15%, and 20%, and a control mix without rubber. A 1.5% superplasticizer (SP) was also added to other mixtures with rubber in the same proportions as before. The study was conducted on concrete cubes with dimensions of 100 mm. The physical properties of this sample were observed and compared with a control sample of regular concrete. A series of tests were carried out to measure the density, and compressive strength, of the sample. The ultrasonic pulse velocity (UPV) of the sample was also tested to evaluate its porosity. The results showed that the addition of recycled rubber to the concrete reduced the density and therefore its compressive strength by more than 26% with an increase in the rubber replacement ratio of 20%, while when using SP the resistance decreased by less than 20% for the same replacement ratio. The pulse velocity of the samples decreased with increasing rubber content.The results demonstrated that recycled rubber can be a viable additive for concrete in some applications, providing water resistance and impact load with minimal reductions in weight. This could lead to more environmentally friendly building materials with improved performance.